Implementation of Silent Demonstration Learning Strategy to Improve Elementary Madrasah Students' Learning Outcomes - Defi Antika; Kharis Sulaiman Hasri (Journal of Contemporary Islamic Primary Education, 2024)
This study aims to describe the implementation of Silent Demonstration for MI/SD students and how this activity can integrate students to think critically, creatively, communicatively, and collaboratively. This research uses a type of qualitative research with descriptive methods. Descriptive research, that is, research conducted to determine the value of the independent variable, either one variable or more (independent) without making comparisons or connecting with other variables. Qualitative collection techniques usually use observation, interviews, and documentation. The demonstration strategy carried out in the learning process is a presentation of lessons by demonstrating and demonstrating to students about a certain process, situation, or object, either real or just an imitation. While mute can be interpreted as silent or unable to speak / just remain silent. Researchers are interested in the behavior of students during silent demonstrations where students play a unified role in making sweet tea, especially when carrying out the steps for making sweet tea, meaning that these activities can attract students' attention and follow learning in a fun way.